Analysis of the Effect of Liquidity, Income Tax Expense, and Leverage on Profitability - Miswanto, Miswanto; Jatmiko, Muji Setyo (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This study examines the effect of liquidity, income tax expense, and leverage on profitability. Methodology/approach – The test uses panel data with a population of 103 companies. The research period for 5 years is from 2019 to 2023. The purposive sampling method was used, so the sample data was 170 observations. The data uses a combination of time series data and panel data. Findings – The results showed that liquidity has no effect on profitability and has a negative direction. Income tax expense has a significant positive effect on profitability. Leverage has a significant negative effect on profitability. Novelty/value – This research contributes to making a practitioner reference for decision-making in increasing profitability and becoming a theoretical reference for further research. The relevance of these results helps financial managers make strategic decisions to manage the company's financial resources. High liquidity indicates an accumulation of unproductive assets. Financial managers can plan tax strategies. The relevance of the results helps financial managers determine the optimal level of leverage. High leverage can increase the risk of default. While low leverage can indicate a heavy dependence on equity.